Reconsidering barriers to wind power projects: community engagement, developer transparency and place. Issue 3 (4th May 2018) - Firestone, Jeremy; Hoen, Ben; Rand, Joseph; Elliott, Debi; Hübner, Gundula; Pohl, Johannes
ABSTRACT: In 2016, we undertook a nationally representative wind power perceptions survey of individuals living within 8 km of over 600 projects in the United States, generating 1705 telephone, web, and mail responses. We sought information on a variety of topics, including procedural fairness and its relationship to project attitude, the foci of the present analysis. We present a series of descriptive statistics and regression results, emphasizing those residents who were aware of their local project prior to construction. Sample weighting is employed to account for stratification and non-response. We find that a developer being open and transparent, a community being able to influence the outcome, and having a say in the planning process are all statistically significant predictors of a process perceived as being 'fair, ' with an open and transparent developer having the largest effect. We also find developer transparency and ability to influence outcomes to have statistically significant relationships to a more positive attitude, with those findings holding when aesthetics, landscape, and wind turbine sound considerations are controlled for. The results indicate that jurisdictions might consider developing procedures, which ensure citizens are consulted and heard, and benchmarks or best practices for developer interaction with communities and citizens.